2009
DOI: 10.1590/s0103-84782009000100025
|View full text |Cite
|
Sign up to set email alerts
|

Intoxicação espontânea pelas larvas de Perreyia flavipes em bovinos no Estado de Santa Catarina, Brasil

Abstract: Intoxicação espontânea pelas larvas de Perreyia flavipes (Pergidae) em bovinos no estado de Santa Catarina.Ciência Rural, v.39, n.1, jan-fev, 2009. Ciência Rural, Santa Maria, v.39, n.1, p.163-166, jan-fev, 2009 ISSN 0103-8478

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 7 publications
1
9
0
5
Order By: Relevance
“…However, all of these plants were neither native to Paraíba nor found in the paddocks where the outbreaks had occurred. Similar intoxications were also caused by Perreyia flavipes larvae (RAYMUNDO et al, 2009;TESSELE et al, 2012), but these were not observed in the pastures.…”
Section: Discussionmentioning
confidence: 62%
“…However, all of these plants were neither native to Paraíba nor found in the paddocks where the outbreaks had occurred. Similar intoxications were also caused by Perreyia flavipes larvae (RAYMUNDO et al, 2009;TESSELE et al, 2012), but these were not observed in the pastures.…”
Section: Discussionmentioning
confidence: 62%
“…sões macroscópicas e microscópicas são semelhantes aos descritos na intoxicação por P. flavipes em bovinos (Dutra et al 1997, Riet-Correa et al 1998, Soares et al 2008, Raymundo et al 2009), ovinos (Dutra et al 1997, Raymundo et al 2008, caprinos (Tramsborg et al 1987) e experimentalmente em suínos (Soares et al 2001).…”
Section: Resultsunclassified
“…Os distúrbios neuromusculares manifestados pelos suínos no presente trabalho foram observados, também, em bovinos, ovinos e experimentalmente em suínos intoxicados por essa lagarta (Dutra et al 1997, Riet-Correa et al 1998, Soares et al 2001, Soares et al 2008, Raymundo et al 2008, Raymundo et al 2009). Estes sinais caracterizam a encefalopatia hepática e podem ser conseqüência de hipoglicemia ou fatores detoxificantes do sistema hepático, levando ao acúmulo dos aminoácidos e amônia, ou de acetilcolina, ou liberação de produtos de degradação (Radostits et al 2002).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Larvae have been linked to spontaneous poisoning and deaths in different species and countries including the following: larvae of Lophyrotoma interrupta (Pergidae) poisoning cattle and sheep in Australia (Da-dswell et al 1985, larvae of Arge pullata (Argidae) poisoning sheep and goats in Denmark (Thamsborg et al 1987), larvae of Perreyia lepida (Pergidae) suspected of poisoning pigs in Brazil (Camargo, 1955 ), and larvae of Perreyia ϔlavipes (Pergidae) poisoning cattle and sheep in Uruguay (Dutra 1997 as well as cattle (Raymundo et al . 2009, Soares et al 2008, sheep (Raymundo et al 2008) and pigs (Jonck et al 2010) in Brazil.…”
Section: Introductionmentioning
confidence: 99%